Czy sieć zastąpi szkołę i rodziców w edukacji i wychowaniu? - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The core of the analysis is countering the myth that allegedly using new communications technologies by children and youths is toxic to their development. In the post-modern world, children enter into partner and educational relationships with their parents specifically thanks to their better abilities to use new media. Changes the science of upbringing and education management are also necessary.